2020
DOI: 10.3389/fgene.2020.570816
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Chlorophyll Degradation Triggers the Pod Degreening of “Golden Hook,” a Special Ecotype in Common Bean (Phaseolus vulgaris L.)

Abstract: To reveal genetic factors or pathways involved in the pod degreening, we performed transcriptome and metabolome analyses using a yellow pod cultivar of the common bean “golden hook” ecotype and its green pod mutants yielded via gamma radiation. Transcriptional profiling showed that expression levels of red chlorophyll catabolite reductase ( RCCR , Phvul.008G280300 ) involved in chlorophyll degradation was strongly enhanced at an early stage (2 cm long) in wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Similar results were observed in the present study ( Figures 2B , C ). Many studies have shown that flavonoids, carotenoids, and anthocyanins may be involved in plant coloration (Hu et al, 2020 ; Jiang et al, 2020 ; Wei et al, 2021 ). In P. violascens cv.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in the present study ( Figures 2B , C ). Many studies have shown that flavonoids, carotenoids, and anthocyanins may be involved in plant coloration (Hu et al, 2020 ; Jiang et al, 2020 ; Wei et al, 2021 ). In P. violascens cv.…”
Section: Discussionmentioning
confidence: 99%
“…(2007). As known, the expression of carotenoids in fruits can occur in two ways: through the synthesis of the pigments, concomitant with chlorophyll degradation, or through unmasking, a result of chlorophyll degradation (Chitarra & Chitarra, 2005; Hu et al ., 2020). The loss of greenish coloration, present in fruits at stage 1, suggests chlorophyll degradation.…”
Section: Discussionmentioning
confidence: 99%
“…"Golden Hook" beans are a low-fat and low-sodium healthy vegetable with full seeds, bright pod color, and little fiber content and are rich in carbohydrates, mineral elements, protein plant sterols, flavonoids, and other phytochemicals beneficial to health (Tor-Roca et al, 2020). In preliminary research, we found that the variety is prone to color change, turning purple, fading, and decay with a storage period of 3-4 days at 20 • C. The color change is a direct reflection of the senescence stage (Khaliq et al, 2021;Hu et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…In preliminary research, we found that the variety is prone to color change, turning purple, fading, and decay with a storage period of 3–4 days at 20°C. The color change is a direct reflection of the senescence stage (Khaliq et al., 2021; Hu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%